刑法上作為與不作為之區分 Distinction Between Acts and Omissions - 周漾沂 Yang-Yi Chou (Kējì Fǎxué Pínglùn, 2014)
本文主題是作為與不作為的區分。在檢視各種流行的區分標準之後，本文提出一種立基於人際觀點的作為與不作為定義：作為是從個人法權領域輸出風險到他人法權領域之中；不作為是個人未撲滅他人法權領域中、與個人無關的既有風險。由於上開定義並不拘泥於事實現象，因此可以妥適地解決各種內含多重詮釋可能之行止形式的疑難案例類型。 The purpose of this article was to distinguish acts and omissions. After reviewing all the predominant criteria, the author proposed to define acts and omissions from the perspective of the interaction between persons. That is, an act means the exportation of risk from one’s field of rights to another, whereas an omission refers to the non-elimination of existing risk in other’s field of rights. These definitions do not rely on the empirical phenomena; therefore they can solve the difficult cases, where one single activity could be interpreted in different ways.